Uncharted Journey : Promoting Democracy in the Middle East - Ottaway, Marina; Carothers, Thomas, 1956- (Book collections on Project MUSE., 2005)
The United States faces no greater challenge today than successfully fulfilling its new ambition of helping bring about a democratic transformation of the Middle East. Uncharted Journey contributes a wealth of concise, illuminating insights on this subject, drawing on the contributors' deep knowledge of Arab politics and their substantial experience with democracy-building in other parts of the world. The essays in part one vividly dissect the state of Arab politics today, including an up-to-date examination of the political shock wave in the region produced by the invasion of Iraq. Part two and three set out a provocative exploration of the possible elements of a democracy promotion strategy for the region. The contributors identify potential false steps as well as a productive way forward, avoiding the twin shoals of either reflexive pessimism in the face of the daunting obstacles to Arab democratization or an unrealistic optimism that fails to take into account the region's political complexities. Contributors include Eva Bellin (Hunter College), Daniel Brumberg (Carnegie Endowment), Thomas Carothers (Carnegie Endowment), Michele Dunne (Georgetown University), Graham Fuller, Amy Hawthorne (Carnegie Endowment), Marina Ottaway (Carnegie Endowment), and Richard Youngs (Foreign Policy Centre).